Design and validation of mechanomyography and torque measurement acquisition system for skeletal muscle function - Sundaraj, Kenneth; Uwamahoro, Raphael; Feroz, Farah Shahnaz (Seventh Sense Research Group, 2024)
Assessment of muscle function is crucial for mitigating the risks of progressive motor weakness, which can ultimately lead to complete muscle impairment. However, existing technologies using commercial dynamometers are expensive, lack open-source availability and are not portable, limiting their accessibility in research settings. This study presents a cost-effective device to record muscle activity and the corresponding elbow joint torque. The device comprises three primary components:1) transducers for Mechanomyography (MMG), 2) torque signals detection, and 3) an application peripheral interface (API) for data acquisition control, visualization, and recording. Both transducers are integrated into an ATMEL ATMEGA 328. The device was validated on 36 able-bodied participants, measuring their MMG and torque across two sessions. Neuromuscular Electrical Stimulation (NMES) was applied to the Biceps Brachii (BB) muscle to induce elbow flexion. Further, submaximal torque and MMG were obtained using a commercial dynamometer and acceleration sensors for comparison. MMG measurements were observed at a maximum mean power frequency beyond 25Hz, while the torque information was found at 10 - 15 % of the Maximum Isometric Contraction (MVIC) induced by NMES. The measurement reliability was assessed using an Interclass Correlation Coefficient (ICC2,1) for elbow joint flexion torque (TQ RMS) and MMG RMS, yielding values between 0.522 and 0. 828. The ICC for the torque measurement device was 0.839, with SEM varying from 3.963 Nm to 11.149 Nm at a CV % of 2.565 to 13.123. These results underscore the potential of the developed device as a reliable, cost-effective alternative, with the added benefit of being replicable using locally available, low-cost electronics.